Strategi Guru PAI dalam Mengatasi Kesulitan Belajar dalam Pembelajaran Pendidikan Agama Islam - Nurul Havista; Zahara Zahara; Taufik Rahman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education (PAI) plays an important role in the formation of students' character and understanding of religious teachings. However, in practice, not a few students face difficulties in understanding PAI material, both in terms of cognitiveness and affective. These difficulties can be caused by a variety of factors, such as differences in academic ability, lack of motivation, or socio-cultural problems. Therefore, the right strategy from PAI teachers in overcoming learning difficulties is very necessary. This article aims to identify various strategies that PAI teachers can apply to help students overcome learning difficulties. Based on a literature review, there are several approaches that have proven to be effective, including the use of varied learning methods, the use of educational technology, the provision of intensive guidance, and the strengthening of student motivation and character. In addition, the importance of constructive evaluation and feedback in the learning process is also one of the keys in improving the effectiveness of PAI learning. By implementing these strategies, it is hoped that the learning difficulties faced by students can be overcome, and the quality of PAI learning can be improved.